Sukuk Issuance in Indonesia: Orientation, Opportunities, and Challenges - Afief El Ashfahany; Dwi Puji Astuti; Aminudin Ma'ruf (Mabsya: Jurnal Manajemen Bisnis Syariah, 2024)
The study aimed to analyze the orientation of Surat Berharga Syariah Negara/Sukuk (SBSN) issuance in accordance with the three main orientations (1) infrastructure development; (2) labor-intensive sector;(3) and optimizing regional potential. This research method uses secondary data qualitative methods. The results of the study indicate that the SBSN project in 2013-2022 has met the orientation towards these three main things. However, in addition to the enormous potential for SBSN to be developed, there are still challenges in developing Sukuk that labor-intensive and optimizing regional potential oriented. This research is expected to be able to increase knowledge about the orientation direction of SBSN issuance, and the results of this study are expected to be input for the Government as the party issuing SBSN and the Ministry or Institution as the recipient of SBSN financing to develop SBSN financing projects oriented to the labor-intensive sector, and optimizing regional potential because these two things can provide great opportunities in Indonesia's economic growth